Major insights from India's minor irrigation censuses: 1986-87 to 2006-07 - Mukherji, Aditi; Rawat, S.; Shah, Tushaar (2013)
Based on data from the four minor irrigation censuses conducted by the Ministry of Water Resources between 1986-87 and 2006-07, this paper points out that India's groundwater sector has slowed down since 2000-01, most markedly in eastern India. It examines the reasons for this and also looks into how farmers have been responding to lowered groundwater tables. Besides identifying some factors that have not changed since the mid-1980s, it emphasises that there are wide regional variations in the country's groundwater economy and management strategies need to be crafted accordingly.